PROBLEMATIKA PEMBELAJARAN DARING PADA MATA PELAJARAN SEJARAH DI SMA NEGERI 3 KOTA JAMBI TAHUN AJARAN 2020/2021 - Pranoto, Nanda Wisnu; Yanto, Fery (Universitas Batanghari Jambi, 2022)
This research began with a policy issued by the Ministry of Education and Culture to carry out the learning process from home by utilizing technology and internet networks (online learning). The sudden policy as an effort to prevent the transmission of the corona virus surprised several parties, especially schools, teachers, and students so that in the online learning process, problems in learning emerged. Therefore, this study aims to 1) find out the problems that arise in the online learning process in history subjects at SMA Negeri 3 Jambi City, 2) find out the solutions taken by the school and teachers in overcoming the problems that exist in the online learning process at history subject at SMA Negeri 3 Jambi City. Researchers apply qualitative research methods, data collection techniques using observation, interviews, and documentation. The data analysis in this study consisted of data reduction, data display, drawing conclusions or verification. The results of the research conducted indicate that there are problems in the online history learning process, both caused by schools, teachers, and students. The solution taken to overcome these problems is the school cooperates with parents, teachers, and related parties. Furthermore, the teacher takes a policy by using learning applications that do not consume a lot of internet data quota. Meanwhile, students make donations to help underprivileged students in the economy in their families so that the learning process can run as an effort to achieve the competencies set out in the curriculum